The clinical phenotypes and therapeutic strategies for stiff skin syndrome: a case series with literature review - Caihui Zhang; Sihao Gao; Zhixing Sun; Tao Wang; Hongmei Song (Orphanet Journal of Rare Diseases)
Abstract Background Stiff skin syndrome (SSS) is a rare, non-inflammatory skin disease with a pronounced restriction in joint mobility. In this study, we aim to report Chinese pediatric patients with SSS in our center and summarize the clinical features of the disease through literature review. Results A retrospective study was conducted on 16 pediatric patients diagnosed with SSS at Peking Union Medical College Hospital between January 2014 and January 2024, based on clinical manifestations, laboratory tests, and skin biopsy findings. Among these cases, two were classified as widespread SSS, and 14 as segmental SSS. Additionally, a review of relevant literature published between January 2000 and January 2024 involving 138 cases of pediatric SSS was also conducted. The clinical characteristics, treatment, and prognosis of these 154 patients were summarized. The age of onset in patients was 2.0(0.5, 4.8) years, with an average age at diagnosis being 9.0(5.0, 13.0) years. Thigh skin sclerosis (81, 52.6%) was the most common manifestation observed in these patients. Joint restriction was present in 55(35.7%) patients. Patients with joint contractures had longer diagnostic delays compared with those without joint contractures. Patients were primarily treated with physical therapy, while some patients received medications such as mycophenolate mofetil (MMF), losartan, and secukinumab. However, the prognosis varied. Conclusion The diagnosis of SSS should involve a thorough investigation of family history, detailed physical examination, comprehensive pathological assessment, genetic testing when applicable, and careful exclusion of other scleroderma-like diseases. Currently, there is limited evidence supporting the use of systemic treatment options targeting the transforming growth factor-β or interleukin-17 pathways (such as MMF, losartan, and secukinumab) to slow disease progression. However, these treatments are not capable of reversing established skin lesions, and further investigations are imperative to assess their therapeutic efficacy in SSS.